Management of depression in patients with schizophrenia spectrum disorders: a critical review of international guidelines. (4th July 2018) - Dondé, C.; Vignaud, P.; Poulet, E.; Brunelin, J.; Haesebaert, F.
Abstract : Objectives: Depression is a frequent but potentially treatable clinical dimension in patients with schizophrenia spectrum disorders (PWS). However, there is a lack of consensual recommendations regarding the optimal strategy to manage depression in PWS. In this study, we aimed to compare the various proposed strategies to define a core set of valid care recommendations for depression management in PWS. Methods: After a systematic search of the literature, the methodological quality of 10 international guidelines from four continents was compared using a validated guideline appraisal instrument (AGREE II). Key recommendations for the management of depression in PWS were subsequently reviewed and discussed. Results: The methodological quality of the guidelines was heterogeneous. Although all guidelines proposed pharmacotherapy, psychosocial interventions were a minor concern. Waiting for antipsychotic effects mostly was recommended during the acute phase of schizophrenia. During the postpsychotic phase of the illness, a switch to a second‐generation antipsychotic and/or the adjunction of an antidepressant were the primary recommendations. Cognitive behavioural therapy and other medications were considered with strong variations. Conclusions: Further studies are needed to strengthen the level of evidence for antidepressive approaches in PWS. The inclusion of PWS as stakeholders is also considered to be a major issue for future guideline development.